Study protocol of a randomized controlled trial of motivational interviewing-based intervention to improve adherence to continuous positive airway pressure in patients with obstructive sleep apnea syndrome: The MotivAir study - Rapelli, Giada; Pietrabissa, Giada; Angeli, Licia; Manzoni, Gian Mauro; Tovaglieri, Ilaria; Perger, Elisa; Garbarino, Sergio; Fanari, Paolo; Lombardi, Carolina; Castelnuovo, Gianluca (Frontiers in Psychology, 2022)
Objective. This study aims to evaluate the effectiveness of the MotivAir program - a phone-based intervention based on Motivational Interviewing (MI) principles and techniques - in enhancing adherence to Continuous Positive Airway Pressure (CPAP) therapy among patients with Obstructive Sleep Apnea Syndrome (OSAS). Methods. A multicenter randomized controlled trial (RCT) design with random allocation at the level of the individual will be conducted to compare the impact of the experimental program (usual care plus MI) with a control group receiving usual care only in improving selected clinical and psychological parameters in the patients. A minimum sample of 80 participants (40 patients per group) will be recruited in each center according to the inclusion criteria. After the initial screening, participants will be randomly assigned to either the experimental group or the control condition. The program will last 180 days and will be delivered by a trained nurse. The impact of the MotivAir program on selected primary (adherence to CPAP in terms of average hours of usage per night and the Apnea-Hypopnea Index, AHI) and secondary (motivation, perceived competence, quality of life, sleepiness, as well as the emotional state, daily life activities, and quality of the social relationships of the person) outcomes will be measured at baseline, and after 1-, 3-, and 6-month from CPAP initiation Discussion. Participants are expected to show an increased level of adherence to CPAP and to acquire the skills and self-confidence necessary to deal with the psychological consequences of their chronic condition.